Вивчення нефропротекторної ефективності ірбесартану у хворих із діабетичною нефропатією - Ларін, О. С.; Зуєв, К. О.; Паньків, В. І.; Юзвенко, Т. Ю.; Кидалова, Г. А.; Когут, Д. Г.; Дашук, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2012)
Renoprotective efficiency the angiotensin-receptor antagonist irbesartan (300 mg QID) in comparison with calcium chenell-blocker amlodipine (10 mg QID) in type 2 diabetic patients with nephropathy at microalbuminuric stage was investigated in open label study. Renal function was evaluated by determination renal functional reserve (RFR) with modified protein tolerance test with instantized milk protein. After 3 months of therapy in patients group received irbesartan (n=30) RFR significantly elevated on 490% (P<0,01), whereas in amlodipine group only non significant 3,6% elevation was observed (P>0,05). At the end of study was observed significantly decrease urine albumin excretion rate at 43% (P<0,05) in irbesartan group. Opposite, in amlodipine group revealed non significant elevation urine albumin excretion rate. Treatment with irbesartan accompanied significant positive alteration many metabolic parameters (glicated haemoglobin (HbA1c), triglycerides and high density lipoproteins). In addition, at the end of the study in irbesartan group, despite to a similar to amlodipine group blood pressure (BP) level decrease (office BP and defined in diurnal BP monitoring), positive influence on diurnal BP rhythm was determined. Thus, nephroprotective action of irbesartan depends not only from angiotensin receptors blockade, but also from many positive metabolic effects and influence on diurnal BP rhythm.